Predicting changes in planning behaviour and physical activity among adults. (March 2015) - Mistry, Chetan D.; Sweet, Shane N.; Latimer-Cheung, Amy E.; Rhodes, Ryan E.
Abstract: Though the effect of action planning upon behavioural enactment is becoming well-established, adherence to planning interventions are modest. Motivations specific to action planning may predict planning behaviour. The primary purpose of the present study was to determine if theory of planned behaviour constructs operationalized for planning could predict change in planning behaviour. The secondary purpose was to determine if planning behaviour predicted changes in physical activity. Participants ( n = 337, M age = 31 ± 5) were adults with intentions to be more active who completed measures of affective and instrumental attitudes towards planning, subjective norms towards planning, perceived behavioural control over planning, intentions to plan, self-reported planning behaviour, intentions to be active and self-reported physical activity at baseline (T1) and after four weeks (T2). Affective attitudes towards planning ( β = 0.10, p < .05), instrumental attitudes towards planning ( β = 0.22; p < .01) subjective norms over planning ( β = 0.12, p < .01) and perceived behavioural control over planning ( β = 0.53, p < .01) predicted intentions to plan (adj. R 2 = 0.66). Intentions to plan ( β = 0.16, p < .05) and intentions to be active ( β = −0.25, p < .05) predicted change in planning behaviour (R 2 change = 0.03). Planning behaviour ( β = 0.27, p < .05) predicted change in physical activity ( R 2 change = 0.07). Planning behaviour appears to have its own motivations distinct from those of physical activity. Future interventions should target planning behaviour along with its motivations and control beliefs to increase rates of planning. The theoretical underpinnings of the TPB are of value for understanding both planning behaviour and physical activity. Highlights: TPB variables operationalized for planning predicted intentions to plan. Intentions to plan were a stronger predictor of planning than intentions to be active. Planning behaviour predicted changes in physical activity. Planning behaviour has its own motivations distinct from those of physical activity.